Vessel Density and Structural Measurements in Primary Angle-Closure Suspect Glaucoma Using Optical Coherence Tomography Angiography. (2nd December 2020) - Zha, Yi; Chen, Juanjuan; Liu, Shuyu; Zhuang, Jinfei; Cai, Jianqiu
Abstract : Purpose . To measure the macular retinal vessel density (VD) and peripapillary retinal nerve fiber layer (RNFL) in primary angle-closure suspects (PACS) by Angio-OCT to be compared with normal subjects. Methods . Primary angle-closure suspect patients and normal subjects were enrolled in this study. The demographic and clinical characteristics of all subjects, such as RNFL thickness, retinal vessel density, and ocular perfusion pressure, were compared. Results . No significant difference was found in both groups on age, sex distribution, intraocular pressure (IOP), and retinal vessel density. The PACS group exhibited significantly thicker RNFL thickness compared with the control group. The deep vessel density was negatively associated with age (P = − 0.034 ), while IOP had negative association with ACD (P = − 0.019 ). OPP was independently associated with RNFL (B = 0.334, P = 0.038 ) in the PACS group. Conclusions . OCTA showed significant thicker change on RNFL in the PACS group. Only OPP was independently associated with RNFL in the PACS group.